Effects of graphite on mechanical properties of stone mastic asphalt pavement - Kök, Baha Vural; Yılmaz, Mehmet; Erkuş, Yunus (My University, 2017)
Hot mix asphalt needs to be developed to resist particular permanent deformations like rutting and thermal cracking due to increased traffic volumes and vehicle loads. Additives such as carbon black, graphite, carbon fibers are used in the mixture or the binder for improving the mechanical features of asphalt. In this article, the effects of graphite used for developing the mechanical properties of asphalt have been investigated in mixtures tests. Therefore, Marshall stability, indirect tensile stiffness modulus and indirect tensile fatigue tests were performed to bituminous mixtures modified with three different proportions of graphite by weight of bitumen. Stone mastic asphalt mixtures which were manufactured with pure and modified bitumen were aged in different time intervals in the oven. In conclusion, it has defined that Marshall stability values have declined. It has been determined that there is no significant difference in the time-dependent deformation behavior of the original and aged samples in pure and different graphite content although the stiffness modulus and load repeat number of the samples increased with the rise of the aging time. These results shown that graphite generally used for improving the thermal properties in literature were also determined to contribute to mechanical properties of mixtures.
Grafitin taş mastik asfalt kaplamanın mekanik özelliklerine etkisi
Makale - Yabancı Dilde Makale
Keywords: Graphite; Stone mastic asphalt; Aging; Mechanical properties; Bitumen; Pavement